Studi Literatur: Meningkatkan Keterampilan Berkomunikasi dengan Public Speaking - Galih, Hasbullah Salim; Hayati, Istaufani Halawatul; Fatimah, Adelia Nur (Indo-MathEdu Intellectuals Journal, 2024)
Communication is an activity that cannot be separated from humans as social creatures, both between individuals and groups. Communication is a person's way of conveying ideas, messages, or thoughts and opinions involving two or more people. This research aims to explain the need to improve communication or public speaking skills as well as solutions for overcoming problems when communicating in public. This research method is a literature study by collecting data or information through books and scientific journals which are analyzed based on existing problems. Sources of information were obtained from research conducted by Taufik R. Talalu, Panir Selwen et al., Ayi Najmul Hidayat and Hasbullah Iau, as well as books written by Dr. Anna Gustina Zainal. Topics discussed in this research include the importance of learning public speaking, inhibiting factors, and solutions to overcome these problems. The research results show that by learning public speaking, a person's self-confidence can grow, and this is very much needed in forming human resources who are skilled at speaking in public both in the academic and professional fields